2021
DOI: 10.1681/asn.2020081242
|View full text |Cite
|
Sign up to set email alerts
|

Association between Longer Travel Distance for Transplant Care and Access to Kidney Transplantation and Graft Survival in the United States

Abstract: BackgroundTransplant candidates may gain an advantage by traveling to receive care at a transplant center that may have more favorable characteristics than their local center. Factors associated with longer travel distance for transplant care and whether the excess travel distance (ETD) is associated with access to transplantation or with graft failure are unknown.MethodsThis study of adults in the United States wait-listed for kidney transplantation in 1995–2015 used ETD, defined as distance a patient travele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…However, in their study, travel was associated with a higher rate of living donor transplant, but a lower likelihood of deceased donor transplant, which is in contrast to our findings. 10 In a sensitivity analysis, we calculated ETD as was done in that study and found that a higher ETD was associated with a higher likelihood of deceased donor transplant in our cohort, consistent with our main analyses. One likely explanation for the differences observed Another potential explanation for the increased access to deceased donor transplant attained by travelers in the post-KAS era is the way that we handled multiple listings in analyses.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, in their study, travel was associated with a higher rate of living donor transplant, but a lower likelihood of deceased donor transplant, which is in contrast to our findings. 10 In a sensitivity analysis, we calculated ETD as was done in that study and found that a higher ETD was associated with a higher likelihood of deceased donor transplant in our cohort, consistent with our main analyses. One likely explanation for the differences observed Another potential explanation for the increased access to deceased donor transplant attained by travelers in the post-KAS era is the way that we handled multiple listings in analyses.…”
Section: Discussionsupporting
confidence: 85%
“…To facilitate comparison of our result to prior studies that have examined similar outcomes using geographic distance, rather than TRR catchment areas, we conducted a sensitivity analysis using excess travel distance (ETD) as the travel metric, as has been previously described. 10 We calculated the distance from the patient's home ZIP code to the closest active adult transplant center (>25 waitlist registrations for patients older than 18 in the study period) and the distance to the center at which the patient was listed. To calculate ETD, we subtracted the distance to the closest center from the distance traveled.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Determinants of delays in time to transplantation differed substantially by racial/ethnic group [ 192 , 193 ]. A decreased likelihood of deceased donor transplantation was also associated with long travel distances to the transplant center [ 194 ]. VA-insured and Medicare/Medicaid-insured patients were less likely to be placed on the waitlist and less likely to receive transplants than patients with private insurance.…”
Section: Resultsmentioning
confidence: 99%